2018
DOI: 10.3389/fimmu.2018.01056
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Adults Is Associated With Plasma Concentrations of Inflammatory Mediators but Not With Lymphocyte Subpopulations

Abstract: Frailty denotes a multidimensional syndrome that gives rise to vulnerability to stressors and leads to an increase of the age-related decline of different physiological systems and cognitive abilities. Aging-related alterations of the immune system may compromise its competence culminating in a chronic low-grade inflammation state. Thus, it has been proposed that frailty is associated with alterations in the concentration of pro-inflammatory molecules and in different lymphocyte subpopulations. To provide furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 51 publications
5
57
3
Order By: Relevance
“…Our data support past studies that have identified the biological underpinnings of frailty as one of immune activation, with effects that linger into the early posttransplant time frame . There is substantial evidence pointing to frailty as a heightened inflammatory state, and biomarkers, such as sTNF‐RII, have even been found to be predictive of frailty status . These past findings of immune activation in frail patients are consistent with our observation of increased rates of ACR among this cohort of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our data support past studies that have identified the biological underpinnings of frailty as one of immune activation, with effects that linger into the early posttransplant time frame . There is substantial evidence pointing to frailty as a heightened inflammatory state, and biomarkers, such as sTNF‐RII, have even been found to be predictive of frailty status . These past findings of immune activation in frail patients are consistent with our observation of increased rates of ACR among this cohort of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Low lymphocyte counts predicted the progression with frailty and this effect has been linked to a deterioration of muscular activity, which is traditionally involved in the physiopathology of frailty syndrome [63,64]. Several studies support the association between lymphopenia and inflammation/immunosuppression, which are both crucial mechanisms linked to frailty [65,66]. A recent observational prospective single-center study in patients with coronary disease showed that in multivariate analysis, lymphocyte counts were inversely related to the odds of frailty, with an exponential increase in risk [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is largely unknown how changes in the immune cellular composition differ between individuals who age in good health from those who become frail at a relatively early age. Several studies have been performed on this subject, but some of these were done in the extreme elderly of 85 years old or above [5], while others focused on a limited set of lymphocyte phenotypes [6][7][8]. Importantly, few studies have been performed enumerating a comprehensive set of immune phenotypes in freshly drawn whole blood samples.…”
Section: Introductionmentioning
confidence: 99%